PERAN SISTEM IMUN TERHADAP TERJADINYA PNEUMONIA TERKAIT STROKE - Al Rasyid* (NEURONA, 2019)
ASSOCIATED PNEUMONIA SAP IS ONE OF THE MEDICAL COMPLICATION WHICH ASSOCIATED WITH HIGH MORTALITY RATE SEVERAL STUDIES CONCLUDE TWO FACTORS INVOLVE SIGNIFICANTLY IN PATHOPHYSIOLOGY OF SAP ONE OF WHICH IS IMMUNODEPRESSION STATE